Myeloid cells as IFNα producers in systemic lupus erythematosus - Kuga, Taiga; Chiba, Asako; Murayama, Goh; Miyake, Sachiko (Frontiers in Immunology, 2025)
Type I interferons (IFNs) play crucial roles in the pathogenesis of systemic lupus erythematosus (SLE). Plasmacytoid dendritic cells (pDCs) stimulated by Toll-like receptor (TLR) pathways have been thought to be the major producers of IFNα in patients with SLE. However, the responsiveness of pDCs from SLE patients to stimuli that produce IFNα differs depending on the type of TLR pathway involved. In addition to pDCs, monocytes from SLE patients were found to produce IFNα when responding to the cGAS-STING pathway. Here, we outline the major pathways that induce IFNα production by myeloid cells in SLE, and the possible mechanisms by which IFNα overproduction occurs by these cells. Finally, we discuss the current and future therapeutic strategies to regulate IFNα production in patients with SLE.